Pengaruh Green Marketing dan Brand Image terhadap Keputusan Pembelian Fore Coffee (Survei pada Konsumen Fore Coffee Cabang Soekarno Hatta Malang) - Muhammad Aditya; Musthofa Hadi; Achmad Zaini (INDO PUBLISHING, 2026)
Growing public awareness of environmental issues encourages changes in consumer behavior when choosing products that are of high quality and demonstrate a commitment to sustainability. The increasingly competitive coffee shop industry encourages companies to create differentiation through green marketing and a strong brand image to influence purchasing decisions. This study aims to examine the effect of green marketing and brand image on purchasing decisions at Fore Coffee Soekarno Hatta Branch, Malang. Using a quantitative approach, data were collected from 97 respondents selected by purposive sampling. Data were analyzed using multiple linear regression and hypothesis testing (t-test and F-test) with SPSS. The results showed that green marketing partially had a positive and significant effect on purchase decisions (t-value 3.741 > 1.985; sig. 0.000 < 0.05), brand image partially had a positive and significant effect (t-value 6.156 > 1.985; sig. 0.000 < 0.05), and both variables simultaneously had a positive and significant effect (F-value 65.735 > 3.093; sig. 0.000 < 0.05). The coefficient of determination (R²) of 57.4% indicates that green marketing and brand image explain purchase decisions. This study concludes that green marketing and brand image contribute to increasing consumer purchasing decisions at Fore Coffee Soekarno Hatta Branch, Malang.